Sistem Informasi Sekolah (SIKOLA) Berbasis Website Pada SMAS Sandikta - Ficky Fathurrahman Saputra (Informatics and Computer Engineering Journal, 2022)
The use of information systems in the field of education in Indonesia, especially in schools, can be said to be still uneven and maximal. SMA Sandikta is a private high school that has started to use an information system but it is not optimal and has not been integrated as a whole, both in the management process and the teaching and learning process. There is still a manual system that is running until now, making the existing system less effective and efficient at SMAS Sandikta. By conducting research that aims to achieve an increase in quality at SMAS Sandikta and the creation of an integrated information system, an information system is needed which is expected to make the entire process, both the management process and the teaching and learning process more effective and efficient. Of the many methods the author uses software development methods, namely the waterfall method and data collection methods such as interviews, observations, documentation and questionnaires to find the shortcomings of the system that has been running so far. Based on this, the author presents a website-based information system that can support the efficiency program for room requirements for document storage, support the paperless program, create a system design in a school information system for principals, teachers, administration, students and parents of students and reduce the occurrence of errors in the delivery of data information and make the whole process, both the management process and the teaching and learning process, becomes more effective and efficient.